Aberrantly expressed long noncoding RNAs as potential prognostic biomarkers in newly diagnosed multiple myeloma: A systemic review and meta‐analysis. (4th September 2022) - Qin, Jiading; Ke, Bo; Liu, Tingting; Kong, Chunfang; Li, Anna; Fu, Huan; Jin, Chenghao
Abstract: Background: Numerous studies have manifested long noncoding RNAs (lncRNAs) as biomarkers to determine the prognosis of multiple myeloma (MM) patients. Nevertheless, the prognostic role of lncRNAs in MM is still ambiguous. Herein, we performed a meta‐analysis to evaluate the predictive value of aberrantly expressed lncRNAs in MM. Methods: A systemic literature search was performed in PubMed, EMBASE, Cochrane, and Web of Science databases until October 9, 2021, and the protocol was registered in the PROSPERO database (CRD42021284364). Our study extracted the hazard ratios (HRs) and 95% confidence intervals (CIs) of overall survival (OS), progression‐free survival (PFS), or event‐free survival (EFS). Begg's and Egger's tests were employed to correct publication bias. Result: Twenty‐six individual studies containing 3501 MM patients were enrolled in this study. The results showed that aberrant expression of lncRNAs was associated with poor OS and PFS of MM patients. The pooled HRs for univariate OS and PFS were 1.48 (95% CI = 1.17–1.88, p  < 0.001) and 1.30 (95% CI = 1.18‐1.43, p  < 0.001), respectively, whereas the pooled HRs for multivariate OS and PFS were 1.50 (95% CI = 1.16‐1.95, p  < 0.001) and 1.59 (95% CI = 1.22‐2.07, p  < 0.001), respectively. Subgroup analysis suggested that MALAT1, TCF7, NEAT1, and PVT1 upregulation were associated with poor OS ( p  < 0.05), PVT1, and TCF7 upregulation were implicated with worse PFS ( p  < 0.05), while only TCF7 overexpression was correlated with reduced EFS ( p  < 0.05). Moreover, the contour‐enhanced funnel plot demonstrated the reliability of our current conclusion, which was not affected by publication bias. Conclusion: Aberrantly expressed particular lncRNAs are critical prognostic indicators in long‐term survival as well as promising biomarkers in progression‐free status. However, different cutoff values and dissimilar methods to assess lncRNA expression among studies may lead to heterogeneity.